Supporting Primary Care Professionals to Stay in Work During the COVID-19 Pandemic: Views on Personal Risk and Access to Testing During the First Wave of Pandemic in Europe - Wanat, Marta; Hoste, Melanie; Gobat, Nina; Anastasaki, Marilena; Böhmer, Femke; Chlabicz, Slawomir; Colliers, Annelies; Farrell, Karen; Karkana, Maria-Nefeli; Kinsman, John; Lionis, Christos; Marcinowicz, Ludmila; et al. (Frontiers in Medicine, 2021)
Background Minimising primary care professionals’ (PCPs) risk of SARS-CoV-2 infection is crucial, to ensure both their safety but a functioning health care system. PCPs’ perspectives on the support they needed in the early stages of a public health crisis can inform future preparedness. Aim To understand PCPs’ experiences of providing care during the COVID-19 pandemic, with focus on personal risk from COVID-19 and testing. Design and Setting Qualitative study using semi-structured interviews with PCPs in England, Belgium, the Netherlands, Ireland, Germany, Poland, Greece and Sweden, between April and July 2020. Method Interviews were analysed using a combination of inductive and deductive thematic analysis techniques. Results Eighty interviews were conducted, showing that PCPs tried to make sense of their risk of both contracting and severity of COVID-19 by assessing individual risk factors and perceived effectiveness of Personal Protective Equipment (PPE). They had limited access to PPE yet continued providing care as their “duty”. Some PCPs felt that they were put in high-risk situations when patients or colleagues were not flagging symptoms of COVID-19. Not having access to testing in the initial stages of the pandemic was somewhat accepted but when available, was valued. Conclusion Access to adequate PPE and testing, as well as training for staff and education for patients about the importance of ensuring staff safety is crucial. Given PCPs’ varied response in how they appraised personal risk and their tolerance for working, PCPs may benefit from the autonomy in deciding how they want to work during health emergencies.